Individual and environmental factors associated with green exercise in urban and suburban areas. (January 2019) - Pyky, Riitta; Neuvonen, Marjo; Kangas, Katja; Ojala, Ann; Lanki, Timo; Borodulin, Katja; Tyrväinen, Liisa
Abstract: In this study, we mainly aimed to explore the associations of personal and socio-demographic factors, and the supply of green areas and built sports facilities with green exercise (GE). We also compared the residents of the core urban area and suburban areas according to the level of leisure time physical activity (LTPA) they had. A population-based sample of 3730 adults (aged 25–101 y) from Finland, filled out a questionnaire in 2015. Variables describing the supply of green areas and built sports facilities were objectively calculated. The green areas were classified into small (<25 ha), middle-sized (25–150 ha) and large (>150 ha) areas to reflect their qualities for GE. The data analysis methods included multinomial logistic regression, t-, and Chi Square tests. Our results indicate that having a short distance to at least a middle-sized green area and high nature relatedness are important for participation in GE, both in core urban and suburban areas. More factors were found to be related to GE in the suburban areas compared to core urban areas and among the low LTPA compared to the high LTPA group. Highlights: Objective qualities e.g. size and connectivity of the green areas were explored. Short distance to a sufficiently large green area is important for green exercise. High nature relatedness is strongly associated with green exercise. Green areas may be essential in activation of adults with low leisure time physical activity.